Changes in total body fat and body mass index among children with juvenile dermatomyositis treated with high-dose glucocorticoids - Amer Khojah; Victoria Liu; Gabrielle Morgan; Richard M. Shore; Lauren M. Pachman (BMC, 2021)
Abstract Objective High-dose glucocorticoids (GC) remain the primary therapy to induce remission in Juvenile Dermatomyositis (JDM). Studies of the natural history of GC associated weight gain in children are very limited, especially in the JDM population. This study aims to measure BMI changes in a cohort of JDM subjects over 60 months and to examine the changes in body composition by DXA. Methods We included all subjects with JDM who had 5 years of follow-up data and multiple DXA studies. BMI and total body fat (TBF) percentiles were calculated based on the CDC published percentile charts. To study the natural history of weight gain and TBF, we assessed the data at four-time points (T0 = baseline, T1 > 1.5 years, T2 = 1.51-3.49 years, T3 = 3.5-5 years). Results 68 subjects (78% female, 70% white) were included in this retrospective study. Paired T-test showed a significant increase in the mean BMI percentile by 17.5 points (P = 0.004) after the initiation of medical treatment, followed by a gradual decrease over the study period. However, the TBF percentile did not change over the study period. TBF in the last visit (T3) had a strong correlation with the T1 BMI, and T1 TBF percentile (correlation coefficients 0.63, 0.56 P < 0.001, 0.002 respectively). Also, there was a positive correlation (correlation coefficients 0.39, P = 0.002) between the TBF percentile and muscle DAS but not the skin DAS. Conclusions Although the BMI percentile decreased throughout the study, the TBF percentile remained high until the end of the study (60 months). This finding raises the concern that some of the reduction in the BMI percentile could reflect a drop in the lean body mass from muscle wasting rather than actual fat loss.